2009
DOI: 10.12962/j20882033.v20i4.83
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Urea and Zeolite for Slow Release Fertilizer using Orbiting Screw Mixer

Abstract: Slow release fertilizer (SRF) of urea is prepared by using zeolite as the matrix. Mixing of urea and zeolite is carried out in orbiting screw mixer. The effects of rotation speed and orbital speed of the mixer and particle size on power consumption, homogeneity, mixing time and specific energy consumption are evaluated. The experimental results show that higher orbital speed gives higher power consumption. Power consumption is dominated by mixer rotation motion. Smaller particle size needs higher power for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mixing urea-natural zeolite powder using a modified orbiting screw mixer with three particle-size groups (50-60, 60-80 and 80 mesh) with variations in rotation and orbital speeds has been previously conducted and evaluated [6]. It was reported that the lowest energy consumption is obtained at an orbital speed of 5 rpm, a rotation speed of 50 rpm, and a particle size of 50-60 mesh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixing urea-natural zeolite powder using a modified orbiting screw mixer with three particle-size groups (50-60, 60-80 and 80 mesh) with variations in rotation and orbital speeds has been previously conducted and evaluated [6]. It was reported that the lowest energy consumption is obtained at an orbital speed of 5 rpm, a rotation speed of 50 rpm, and a particle size of 50-60 mesh.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mixing time for fine particles is longer than that for coarse particles, and there is a trade-off between power consumption and mixing time. The optimum specific energy consumption is achieved by considering both of these parameters [6]. Among all the variations, the lowest specific energy consumptions was obtained by the combination of orbital and rotation speeds of 5 and 67.5 rpm and an air flow rate of 10 l/min with a 60-80 mesh particle size.…”
Section: Energy Consumptionmentioning
confidence: 99%